Students’ Well-Being: The Mediating Roles of Grit and School Connectedness - Han, Kunni (Frontiers in Psychology, 2021)
A remarkable point in previous decades in every aspect of life is well-being which is also effective in academic settings, and it is consistent with positive psychology, in which one can recognize how to make everything pleasing. Moreover, grit is another noteworthy point in the process of learning which is at the center of researchers’ attention in last years as a result of its long-term eminence. In addition, school connectedness is another important factor that was found to be positively related to students’ well-being. Therefore, the current review endeavors to emphasize the mediating role of these two constructs, grit and school connectedness on students’ well-being. Successively, some implications are proposed for educators, learners, teacher educators, and materials developers.